Physical performance and technical-tactical aspects in 4 vs. 4 small-sided games across various field formats among professional soccer players - Ispyrlidis, I.; Gourgoulis, V.; Mitrotasios, M.; Mantzouranis, N. (Journal of Physical Education and Sport, 2024)
This study assessed the impact of varying pitch dimensions during 4 vs. 4 small-sided games on both physiological performance and technical-tactical aspects among professional soccer players. The sample comprised eight (n= 8) male players from a Greek Superleague team, with an average age of 20 ± 1.5 years, body mass of 73.9 ± 6.4 kg, and stature of 179.4 ± 46cm. The players trained in 4 vs. 4 small-sided games with 1 goalkeeper, played in 4×5 min intervals with a 5 min rest period, across three playing formats: full pitch - half pitch - quarter pitch. In the small-sided games training, the players` heart rate and blood lactate were measured in real-time, while both video and visual observation recorded their technical-tactical parameters. During the 4vs4 training in the quarter pith, the players` blood lactate concentration ranged from 6.02 to 6.65mmol/l-1. Additionally, in 4 vs. 4 small-sided games in the half pitch the players` blood lactate ranged from 8.24 to 9.42mmol/l-1, while their blood lactate concentration was measured as high as 9.65-11.28mmol/l-1 during the whole pitch games. In contrast, no differences were recorded in the players` heart rate in any one of the Small- Sided-Games in the three training formats. Regarding the players technical-tactical parameters, the current study reported that the smaller the pitch dimension of the small-sided games the greater the amount of the players` mistakes in passes accuracy, 1vs1, shots and goal-scored.